KINERJA PEGAWAI DPMPTSP KABUPATEN KLATEN DALAM UPAYA PENINGKATAN JUMLAH PENERBITAN IZIN USAHA - Ningsih Widi Astuti; Amni Zarkasyi Rahman; Retno Sunu Astuti (Journal of Public Policy and Management Review, 2023)
Klaten Regency was recorded as having 54,956 business actors in 2020, however, 5 (five) years since the innovation in issuing business permits which was carried out in 2017, the Klaten Regency DPMPTSP only issued 16,208 IUMK. The aim of this research is to determine the performance of Klaten Regency DPMPTSP employees and the factors that influence efforts to increase the number of business permit issuances. This type of research uses a quantitative approach with descriptive research type. The population of this research is the apparatus at DPMPTSP Klaten Regency, where the sample was determined using a saturated sampling technique. The measuring instrument used is the Likert scale. The results show that quantity gets a score of 67% with a medium score rating, quality gets a score of 53% with a low score rank, time gets a score of 67% with a medium score rank, skills gets a score of 67% with a medium score rank, leadership gets a score of 63% with a score rank low, and organizational culture scored 70% with a medium rating. Some things that need to be improved are monitoring the implementation of SOPs, evaluating the results of the work in question, increasing leader commitment, and facilitating the delivery of aspirations